Peptide nanovesicles formed by the self-assembly of branched amphiphilic peptides - Gudlur, Sushanth; Sukthankar, Pinakin; Gao, Jian; Avila, L. Adriana; Hiromasa, Yasuaki; Chen, Jianhan; Iwamoto, Takeo; Tomich, John M. (My University, 2012)
Peptide-based packaging systems show great potential as safer drug delivery systems. They overcome problems associated with lipid-based or viral delivery systems, vis-a-vis stability, specificity, inflammation, antigenicity, and tune-ability. Here, we describe a set of 15 & 23-residue branched, amphiphilic peptides that mimic phosphoglycerides in molecular architecture. These peptides undergo supramolecular self-assembly and form solvent-filled, bilayer delimited spheres with 50–200 nm diameters as confirmed by TEM, STEM and DLS. Whereas weak hydrophobic forces drive and sustain lipid bilayer assemblies, these all-peptide structures are stabilized potentially by both hydrophobic interactions and hydrogen bonds and remain intact at low micromolar concentrations and higher temperatures. A linear peptide lacking the branch point showed no self-assembly properties. We have observed that these peptide vesicles can trap fluorescent dye molecules within their interior and are taken up by N/N 1003A rabbit lens epithelial cells grown in culture. These assemblies are thus potential drug delivery systems that can overcome some of the key limitations of the current packaging systems.
Citation: Gudlur S, Sukthankar P, Gao J, Avila LA, Hiromasa Y, Chen J, et al. (2012) Peptide Nanovesicles Formed by the Self-Assembly of Branched Amphiphilic Peptides. PLoS ONE 7(9): e45374. https://doi.org/10.1371/journal.pone.0045374
Keywords: Peptide-based packaging systems; Drug delivery systems; Nanovesicles